Avobenzone incorporation in a diverse range of Ru(ii) scaffolds produces potent potential antineoplastic agents. Issue 35 (26th August 2020) - Ryan, Raphael T.; Havrylyuk, Dmytro; Stevens, Kimberly C.; Moore, L. Henry; Kim, Doo Young; Blackburn, Jessica S.; Heidary, David K.; Selegue, John P.; Glazer, Edith C.
Abstract : Four structurally distinct classes of polypyridyl ruthenium complexes containing avobenzone exhibited low micromolar and submicromolar potencies in cancer cells, and were up to 273-fold more active than the parent ligand. Abstract : Four structurally distinct classes of polypyridyl ruthenium complexes containing avobenzone exhibited low micromolar and submicromolar potencies in cancer cells, and were up to 273-fold more active than the parent ligand. Visible light irradiation enhanced the cytotoxicity of some complexes, making them promising candidates for combined chemo-photodynamic therapy.